Effects of nitrogen fertilizer on protein accumulation in basal-middle and apical kernels of different low nitrogen tolerant maize hybrids - Yin, Pi-Jiang; Wang, Xing-Long; Wu, Ya-Wei; Liu, Fan; Tao, Ye; Liu, Qin-Lin; Lan, Tian-Qiong; Feng, Dong-Ju; Kong, Fan-Lei; Yuan, Ji-Chao (Frontiers in Plant Science, 2025)
Selecting low-nitrogen(N)-tolerant maize hybrids represent an effective approach to enhancing nitrogen use efficiency grain yield. However, the impact of nitrogen fertilization on protein accumulation in low-N-tolerant hybrids remain insufficiently explored. In this paper, a two-year field orientation trial was conducted at four nitrogen fertilizer rate with the different low-N-tolerant maize hybrids. The effect of nitrogen fertilization on the accumulation of protein and its fractions different kernels positions of different low-N-tolerant maize hybrids was studied. The results showed that the protein yield of ZH311 maize kernels was significantly higher than that of XY508, especially under low-N conditions (0N and 150N), and was 25.7%-36.2% higher than that of XY508. There was a significant correlation between protein yield and the accumulation of crude protein and protein fractions. Compared with XY508, the crude protein of ZH311 entered the rapid growth stage later and lasted for a relatively shorter period, but it was 50.8%-53.0% higher due to its higher accumulation rates (v2 and v3) in its middle and late stages, especially in the apical grains. Under low-N conditions, the difference in crude protein accumulation between the apical and basal-middle kernels of ZH311 was only 4.3-8.2%, whereas the difference in XY508 was 29.9-37.3%, suggesting that low-N-tolerant maize hybrids improve protein yield by increasing the accumulation of proteins and their fractions in the apical kernels. Nitrogen fertilization had a greater effect on protein accumulation and yield in XY508, especially on the top kernel and protein yield. In the future, more attention should be paid to the effect of apical kernels when breeding high-quality maize hybrids tolerant to low nitrogen.